Quantifying the Speed of Chromatophore Activity at the Single-Organ Level in Response to a Visual Startle Stimulus in Living, Intact Squid - Hadjisolomou, Stavros P.; El-Haddad, Rita W.; Kloskowski, Kamil; Chavarga, Alla; Abramov, Israel (Frontiers in Physiology, 2021)
The speed of adaptive body patterning in coleoid cephalopods is unmatched in the natural world. While the literature frequently reports their remarkable ability to change coloration significantly faster than other animals, there is limited research on the temporal dynamics of rapid chromatophore coordination underlying body patterning in living, intact animals. In this exploratory pilot study, we aimed to measure chromatophore activity in response to a light flash stimulus in seven squid, Doryteuthis pealeii. We video-recorded the head/arms, mantle, and fin when squid were presented with a light flash startle stimulus. Individual chromatophores were detected and tracked over time using image analysis. We assessed baseline and response chromatophore surface area parameters before and after flash stimulation, respectively. Using change-point analysis, we identified 4,065 chromatophores from 185 trials with significant surface area changes elicited by the flash stimulus. We defined the temporal dynamics of chromatophore activity to flash stimulation as the latency, duration, and magnitude of surface area changes (expansion or retraction) following the flash presentation. Post stimulation, the response’s mean latency was at 50 milliseconds (±16.67 milliseconds), for expansion and retraction, across all body regions. The response duration ranged from 217 milliseconds (fin, retraction) to 384 milliseconds (heads/arms, expansion). While chromatophore expansions had a mean surface area increase of 155.06%, the retractions only caused a mean reduction of 40.46%. Collectively, the methods and results described contribute to our understanding of how cephalopods can employ thousands of chromatophore organs in milliseconds to achieve rapid, dynamic body patterning.